Corporations in the political arena: an ethical framework. Issue 2 (11th January 2020) - Barron, Andrew; Stacey, Stephen
Abstract : Purpose: This study aims to explore how firms can configure their organisational architectures in ways that limit ethical transgressions of their corporate political activities (CPAs). Design/methodology/approach: This conceptual work is informed by existing research into organisational architecture and ethical decision-making, combined with illustrative examples of firms' political actions derived from secondary and primary data sources. Findings: Findings suggest that the ways that firms assign decision-making authority and design performance management systems can, depending on their combined configuration, either help or hinder the promotion of ethical CPA practice. Practical implications: The study provides practitioners with a useful tool for reflecting on the organisational levers they can pull to shield their firms from the financial and reputation damage associated with objectionable conduct in their political activities. Originality/value: Whilst previous research studies emphasise the importance of statutory guidelines, self-regulation or corporate codes for promoting ethical CPA, this study argues that organisational design is an important yet overlooked antecedent of a firm's ability to practice CPA ethically and responsibly.